Knowledge of doctors and nurses of the Family Health Strategy about prenatal dental care - Mendes, Gemakson Mikael (2022)
The research aimed to evaluate the knowledge of nurses and doctors inserted in the prenatal care of the basic family health units in São Gonçalo do Amarante in Ceará regarding dental prenatal care. A cross-sectional quantitative and descriptive study was carried out, applied through a questionnaire. Data were tabulated using Microsoft Excel software (2010) and later an inferential and descriptive analysis was performed using the Statistical Package for Social Sciences Software (SPSS) version 22.0. Doctors and nurses knew the importance of dental care during pregnancy, recognizing the influence of oral health during pregnancy. The doctors were more favorable to dental radiography when necessary. Most nurses knew the expression “dental prenatal care”, they felt more satisfied with the maternal and child care offered, and commonly referred the pregnant woman for dental prenatal care. The findings highlight a closer approach between the nurses and oral health care during pregnancy and point to the importance of professional training to offer this type of care.